2017
DOI: 10.3389/fncel.2017.00064
|View full text |Cite
|
Sign up to set email alerts
|

Adiponectin Regulates the Polarization and Function of Microglia via PPAR-γ Signaling Under Amyloid β Toxicity

Abstract: Alzheimer’s disease (AD), characterized by the abnormal accumulation of amyloid beta (Aβ), is gradually increasing globally. Given that AD is considered a neuroinflammatory disease, recent studies have focused on the cellular mechanisms in brain inflammatory conditions that underlie AD neuropathology. Microglia are macrophage cells in the central nervous system (CNS) that are activated in response to Aβ condition. The function of microglia contributes to the neuroinflammation in AD brain, suggesting that micro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
33
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(36 citation statements)
references
References 76 publications
3
33
0
Order By: Relevance
“…1b ). This data is consistent with a recent finding that AdipoR1 knockdown in microglial cell line BV-2 exhibited M1 polarization, pro-inflammatory phenotype, under the basal condition 31 . In summary, AdipoR1 knockdown have shown neurodegeneration-mediated memory dysfunction as well as global AD-like pathologies including insulin signalling dysfunction, proteinopathies and neuroinflammation.…”
Section: Resultssupporting
confidence: 93%
“…1b ). This data is consistent with a recent finding that AdipoR1 knockdown in microglial cell line BV-2 exhibited M1 polarization, pro-inflammatory phenotype, under the basal condition 31 . In summary, AdipoR1 knockdown have shown neurodegeneration-mediated memory dysfunction as well as global AD-like pathologies including insulin signalling dysfunction, proteinopathies and neuroinflammation.…”
Section: Resultssupporting
confidence: 93%
“…Consistent with peripheral inflammatory studies (Satoh et al ., ; Masuda et al ., ), our data suggested that microglial M1 and M2 phenotypes are also regulated by IRF5 and IRF4, respectively. Emerging data have demonstrated the IRF5/4 signaling was implicated in neurodegenerative (Zhu et al ., ; Song et al ., ) and infectious (Takaoka et al ., ; Balkhi et al ., ; Satoh et al ., ; Xuan et al ., ) diseases, and indicated that IRF5/4 are the key determinants for macrophage polarization upon inflammatory stimuli (Al Mamun & Liu, ). The present study found the expression of IRF5/4 in ischemic microglia is up‐regulated in a time‐dependent manner that is closely correlated with M1/2 phenotype, respectively, suggesting microglia share the same mechanism as that in peripheral monocytes to respond to self‐antigens.…”
Section: Discussionmentioning
confidence: 99%
“…The same group also showed that globular adiponectin directly inhibits microglia pro-inflammatory profile in vivo and in vitro (Nicolas et al, 2017) in a mechanism involving AdipoR1 and NF-κB. Adiponectin also modulates microglial activation profile under Aβ toxicity in vitro , via PPARγ activation (Song et al, 2017). Further evidence for the anti-inflammatory actions of adiponectin in the CNS come from a study showing that CTRP9, an AdipoR1 agonist, attenuates neuroinflammation in a mouse model of intracerebral hemorrhage through a AdipoR1/AMPK/NFκB signaling mechanism (Zhao et al, 2018).…”
Section: Adiponectinmentioning
confidence: 98%